Modern Non-Steroidal Anti-Inflammatory Drugs - Gafurovich, Bekchanov Bakhtiyar; Olimovich, Masharipov Otaboy; qizi, Komilova Dilrabo Rakhimboy; Atabaevich, Masharipov Ogabek (Journal of Medical Genetics and Clinical Biology, 2024)
Over the past decade, employees of the departments of pharmacology, general and bioorganic chemistry of the Tashkent State Medical Institute (since 1990, I Tashkent State Medical Institute) have been conducting targeted research to find, study new, more advanced anti-inflammatory drugs in a number of new pyrazole derivatives and related compounds (in general, nutrition more than 300 new drugs were exposed). These studies revealed a number of highly active and low-toxic compounds, and also established the dependence of the anti-inflammatory activity of these compounds on the chemical structure.